Determination Analysis of Hospitals in East Java on Readiness in Facing a Pandemic Based on the WHO Rapid Hospital Readiness Checklist - Atok Irawan; Sentot Imam Suprapto; Ratna Wardani (Journal of Nursing Practice, 2023)
Background: During the COVID-19 pandemic, health service providers, especially hospitals, are expected to be able to optimize all their resources in providing services to patients. Assessment of hospital readiness in dealing with the COVID-19 pandemic is needed to ensure that hospitals continue to maintain and improve the quality of health services and patient safety.